Effect of Celastrus Orbiculatus Extract on proliferation and apoptosis of human Burkitt lymphoma cells - Zhu, Miao; Chu, Zewen; Dai, Xiaojun; Pan, Fan; Luo, Yuanyuan; Feng, Xingyi; Hu, Yaqi; Wang, Haibo; Liu, Yanqing (Frontiers in Pharmacology, 2024)
The lymphoma incidence rate is on the rise, with invasive forms particularly prone to relapse following conventional treatment, posing a significant threat to human life and well-being. Numerous studies have shown that traditional Chinese botanical drug medicine offers promising therapeutic benefits for various malignancies, with previous experimental findings indicating that Celastrus orbiculatus extract effectively combats digestive tract tumors. However, its impact on lymphoma remains unexplored.This study aims to investigate the impact and underlying mechanisms of COE on the proliferation and apoptosis of Burkitt lymphoma cells. We diluted COE in RPMI-1640 medium to create various working concentrations and introduced it to human Burkitt lymphoma Raji and Ramos cells. To evaluate cell viability, we used the CCK-8 assay, and we observed morphological changes using HE staining. We also conducted Annexin V-PI and JC-1 staining experiments to assess apoptosis. By combining the cell cycle experiment with the EDU assay, we gained insights into the effects of COE on DNA replication in lymphoma cells. Using Western blotting, we detected alterations in apoptosis-related proteins. In vivo experiments revealed that following COE intervention, tumor volume decreased, survival time was prolonged, spleen size reduced, and the expression of tumor apoptosis-related proteins changed. Our findings indicate that COE effectively inhibits lymphoma cell proliferation and promotes apoptosis by regulating these apoptosis-related proteins.